Pengaruh Likuiditas, Profitabilitas, Leverage, dan Market Ratio terhadap Dividend Payout Ratio pada Perusahaan Manufaktur - Erna Puspita (Universitas Muhammadiyah Ponorogo, 2017)
Dividend policy is concerned with financial policies regarding what amount cash dividend paid to shareholders and re-invested as retained earnings. The recent research aimed to test empirically various factors is considered to affect dividend policy. The independent variables in his research included Current Ratio (CR), Return on Equity (ROE), Debt to Equity Ratio (DER), and Earning Per Share (EPS). Meanwhile, the dependent variable was Dividend Payout Ratio (DPR). Quantitative research was used as the research design and the data was secondary data. Furthermore, purposive sampling was selected to get the sample. The result was 14 companies that pay dividend continuously during this research conducted on 2012 - 2014 were selected as the sample of this research. Multiple linier regression was used to analyze the data. The results showed that ROE and EPS has a contribution to the DPR, and then CR and DER has no contribution to the DPR.